Voltage-Dependent Anion-Selective Channels and Other Mitochondrial Membrane Proteins Form Diverse Complexes in Beetroots Subjected to Flood-Induced Programmed Cell Death - Rojas-Méndez, Karla J.; Sánchez Segura, Lino; Chagolla, Alicia; Lino, Bárbara; González de la Vara, Luis E. (Frontiers in Plant Science, 2021)
In plants, programmed cell death (PCD) is involved in both the development and in the response to biotic and abiotic aggressions. In early stages of PCD, mitochondrial membranes are made permeable by the formation of permeability transition pores, whose protein composition is debated. Cytochrome c is then released from mitochondria, inducing the degradation of chromatin characteristic of PCD. Since flooding stress can produce PCD in several plant species, the first goal of this work was to know if flooding stress could be used to induce PCD in Beta vulgaris roots. To do this, two months old beet plants were flood-stressed from one to five days, and the alterations indicating PCD in stressed beetroot cells were observed with a confocal fluorescence microscope. As expected, nuclei were deformed, and chromatin was condensed and fragmented in flooded beetroots. In addition, cytochrome c was released from mitochondria. After assessing that flood stress induced PCD in beetroots, the composition of mitochondrial protein complexes was observed in control and flood-stressed beetroots. Protein complexes from isolated mitochondria were separated by native gel electrophoresis, and their proteins were identified by mass spectrometry. The spectra count of three isoforms of voltage-dependent anion-selective channels (VDAC) increased after one day of flooding. In addition, the size of the complexes formed by VDAC was higher in beetroots flood-stressed for one day (~200 kDa) compared with non-stressed ones (~100 kDa). Other proteins, like chaperonin CPN60-2, also formed complexes with different masses in control and flood-stressed beetroots. Finally, possible interactions of VDAC with other proteins were found performing a cluster analysis. These results indicate that mitochondrial protein complexes formed by VDAC could be involved in the process of programmed cell death in flood-stressed beetroots.